Client Transformation for Access to Public Resources - Danunegoro, Rengga Akbar (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2024)
This study analyses the neo-clientelist relationship between largest laskar group in the Purwoboyo region, the Laskar Nusantara Rider, and the party and elites of Prosperous National Party in the Purwoboyo region. Data were collected through in-depth interviews and non-participatory observation as primary sources. In addition, secondary data were gathered from online media literature. Using Hopkin’s (2014) framework, this study finds that the clientelist relationship was established due to a convergence of interests between both sides. The party and elites of the Prosperous National Party in the Purwoboyo region regard the Laskar Nusantara Rider as a vote bank in elections. Conversely, the Laskar Nusantara Rider group perceives clientelism relationship as means of gaining access to public and formal resources via government programmes and social assistance. Furthermore, this study finds that the Laskar Nusantara Rider play a role in distributing public resources, aligning with Torquist (1990) notion of a state-backed client theory.